Leadership Workshop for the Head of Madrasah Ibtidaiyah Ma'arif Educational Institution Bojonegoro Regency - Sri Minarti; M. Tsaqibul Fikri; Farida Isroani; Mita Erliana (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Elementary Madrasah Principal Leadership Workshop is an activity aimed at improving the leadership quality of madrasah principals in carrying out their duties and responsibilities in the madrasah environment. This activity usually includes various materials and training relevant to the role of madrasah principals, such as madrasah management, self-potential development, supervision, and curriculum implementation. Improve madrasah principals' understanding of effective leadership in the madrasah environment. Develop madrasah principals' leadership competencies in various aspects, such as managerial, supervisory, and teacher professional development. Provide strategies and best practices in leading madrasahs to achieve educational goals. Improve the quality of learning and student achievement through effective leadership.